Colors of Gilead : Color-coding as a Means of Power in Margaret Atwood's The Handmaid's Tale and The Testaments - Wallenius, Petra (My University, 2025)
Colors are an integral part of how we perceive the world. Our eyes detect colors automatically, which makes them efficient communicative devices. If you see a text, you can decide not to read it. Contrastingly, if you see a color, you have already perceived it and connected it to your previous knowledge about the functions and meanings it has. A systematic use of colors can therefore act as a powerful tool for subjugation, which is what I found in Margaret Atwood’s novels The Handmaid’s Tale (1985) and The Testaments (2019). In this thesis I study how the systematic use of colors turns into color-coding that labels, distinguishes, and controls people and entities in the fictional Republic of Gilead. Together with other suppressive and restrictive policies, color-coding is a vital part in the creation, execution, and maintenance of theocratic power structures. I examine Gilead’s most important colors and their meanings through Western connotations and explain how these colors are used for color-coding in these novels. Finally, I examine how protagonists with different social statuses perceive the color-coding and analyze how the level of suppression applied to them affects their perspectives. Despite the dystopian echoes these novels have, the main events have a historical background. Together with the interconnectedness of the color palette and the subjugated groups this offers a rich ground for further research, which I propose in the last section.
Keywords: color-coding, Margaret Atwood, dystopia, subjugation